Antibacterial activity of Saponaria officinalis and Zanthoxylum aramatum - G, Veda; T, Mallikarjuna Rao; B, Ganga Rao (International Journal of Pharmacology and Toxicology, 2016)
The present study was carried out to evaluate the antimicrobial properties of two traditional medicinal plant species Saponaria officinalis and Zanthoxylum aramatum belonging to the families Raryophyllaceae and Rutaceae. The root part was selected for the antibacterial activity, and extracts were prepared using soxhlet extraction procedure using different solvents successively. Different extracts of selected plants tested their anti-microbial property using agar well diffusion method at different concentration on standard human pathogenic bacterial strains. The selected plants extracts concentrated dependent bactericidal activity on tested standard bacterial strains. The zones of inhibitions were measured for each concentration of various extracts on each bacterial strain tested in a millimeter (mm). All concentrations of extracts showed minimum zone of inhibition (8mm). The chloroform extracts at 5mg/100µL showed less activity. But, as the concentration increases the bactericidal activity was increased. The extracts showed more activity at 40mg/100µL. Among two plants S. officinalis showed more antibacterial activity. In these, methanol extracts of two plants more competent results along with ciprofloxacin on tested bacterial strains. The extracts also showed more activity on gram-negativeorganisms compared to gram-positiveorganisms. The extracts showed more activity on E. coli and S. typhimurium and lower activity on C. sporogenes and S. pneumoniae. The results of the present study provide the evidence on antibacterial property of selected medicinal plants and there is a scope to further studies on isolation of antimicrobial compounds from these species.
Keywords: Saponaria Officinalis; Zanthophyllum Aramatum; Roots and Antimicrobial Activity.